2021
DOI: 10.1186/s13756-021-00969-w
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and outcomes of bloodstream infections in severe burn patients: a six-year retrospective study

Abstract: Background Infection is the leading cause of morbidity and mortality among burn patients, and bloodstream infection (BSI) is the most serious. This study aimed to evaluate the epidemiology and clinical outcomes of BSI in severe burn patients. Methods Clinical variables of all patients admitted with severe burns (≥ 20% total body surface area, %TBSA) were analyzed retrospectively from January 2013 to December 2018 at a teaching hospital. The Kaplan–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 28 publications
(35 reference statements)
3
13
2
2
Order By: Relevance
“…Our study found that the median time from the burn incident to BSI onset was 32 days and that 84.4% of BSIs occurred after 2 weeks. This finding was different from past studies that reported that the median time from the burn incident to BSI onset was 7 days 4 or 8 days, 12 probably because early aggressive excision of the eschar was performed in our burn center within 2 weeks after the burn. Excising the eschar and covering the wound as early as possible is crucial for infection control in burn patients, 13 and total debridement should be completed within 2 weeks at the latest in our burn center.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our study found that the median time from the burn incident to BSI onset was 32 days and that 84.4% of BSIs occurred after 2 weeks. This finding was different from past studies that reported that the median time from the burn incident to BSI onset was 7 days 4 or 8 days, 12 probably because early aggressive excision of the eschar was performed in our burn center within 2 weeks after the burn. Excising the eschar and covering the wound as early as possible is crucial for infection control in burn patients, 13 and total debridement should be completed within 2 weeks at the latest in our burn center.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings were consistent with the results of previous similar reports. 12 Thus, we should be cognizant of poor BSI outcomes, and that the risk of BSI increases with higher TBSA in burn patients.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the multivariate analysis indicated that MODS and septic shock were closely associated with poor outcomes in immunosuppressed patients with CRGNB-BSI, indicating that the severity of the patient’s disease was closely related to death, which was consistent with some previous studies. 5 , 16 , 21 , 36 In this study, gastrointestinal bleeding often indicated a poor prognosis. A study by Amy et al showed that gastrointestinal bleeding had a negative impact on the short-term survival of patients with BSI.…”
Section: Discussionmentioning
confidence: 77%
“…However, those studies were conducted in certain groups of immunosuppressed patients or for specific microbial infections in different types of immunosuppression. 1,[16][17][18][19] Studies related to CRGNB-BSI in the overall immunosuppressed population are still scarce. This study evaluated the clinical characteristics of immunosuppressed patients with CRGNB-BSI and investigated the prognostic factors in immunosuppression status for the overall population and different subgroups.…”
mentioning
confidence: 99%
“…The risk factors related to death of burn patients are mainly age, burn severity, inhalation injury and nutrition [6][7][8][9]. Some studies have shown that clinicians include in ammatory indicators in early sepsis diagnosis [10,11].…”
Section: Introductionmentioning
confidence: 99%